Obesity problem students from Secondary School No 32 in Bydgoszcz - Magdalena Wittbrodt; Marek Napierała; Rafał Gotowski (Kazimierz Wielki University, 2017)
The aim of this study was to determine the level of youth obesity from School No. 32 in Bydgoszcz, how their nutrition and to provide existing eating habits. The study included 60 girls and 40 boys. The method used in the study is a diagnostic survey. Conclusions from the study are as follows: (1) young people eat irregular meals, (2) favorite snack between meals is a candy and soft drinks, (3) a sedentary lifestyle conducive to the development of obesity and overweight, (4) parents should set a good example for their children, (5) good sports facilities, schools can have an impact on the level of obesity amongst schoolchildren.